Effects of phase-lags, rotation, and temperature-dependent properties on plane waves in a magneto-microstretch thermoelastic medium. Issue 4 (30th March 2021) - Said, Samia M.
Abstract: The present article is aimed at studying the effect of rotation and temperature-dependent properties on plane waves in a homogeneous, isotropic, initially stressed magneto-microstretch thermoelastic. The enunciation is applied to generalized thermoelasticity based on the three-phase-lag model, the Green-Naghdi II theory without energy dissipation as well as the coupled theory. In addition, the thermal conductivity and the modulus of elasticity are taken as a linear function of reference temperature. In order to obtain the stress, displacement and temperature field, the field functions are expressed in terms of normal mode analysis. The distributions of the temperature, stress, as well as other variable fields, are numerically obtained and illustrated graphically for particular cases. Communicated by Francesco Tornabene